Progression of data recording technology and implications for information-sharing across the beef supply chain - Marchek, Audrey Elizabeth (Kansas State University, 2024)
Tracking of whole-herd performance data on virtual platforms has been utilized since the early to mid-1990’s. Primarily established to promote the sales of elite breeding genetics and value-based marketing of live cattle, relatively slow adoption rates, risks associated with information sharing, and overall level of understanding surrounding the use of electronic platforms as a data management tool have presented barriers to increasing information transparency across the beef cattle supply chain. Access to such tools that facilitate improved transfer of information and enhance management practices are crucial to further development of the beef cattle industry and ultimately, the continued creation of quality beef products to exceed heightened industry and consumer expectations. Primary objectives of this project are to build upon the original framework established for the mobile cattle record-keeping application referred to as the “CalfDex”, distribute the platform for beta-testing across a diverse demographic of producers, and continue development of the tool based on feedback received through inquiries and survey responses from users. To examine the efficacy of the information sharing function, arguably the most beneficial aspect of CalfDex, the beta-testing trial was conducted to determine the number of users who had exported and shared cattle information from the mobile application. A combination of exported data and survey results revealed that precisely 90 operations had tested or utilized the data export feature, and that entries for 2,709 head of cattle were recorded. Intriguingly, survey results revealed that only 27 percent of respondents had used the available data storage and export functions, yet 58 percent of participants in the survey indicated a desire to learn more about these features. Further revisions and additional beta-testing trials are necessary to comprehensively evaluate the effectiveness of CalfDex as an information-sharing and animal data management system.
Keywords: Information; Technology; Beef; Supply; Chain